Protein carbamylation in end stage renal disease: is there a mortality effect?. Issue 6 (November 2018) - Kalim, Sahir
Abstract : Purpose of review: Protein carbamylation is a posttranslational protein modification caused, in part, by exposure to urea's dissociation product cyanate. Additional modulators of protein carbamylation include circulating free amino acid levels, inflammation, diet, smoking, and environmental pollution exposures. Carbamylation reactions can modify protein charge, structure, and function, leading to adverse molecular and cellular responses. These changes have been linked to several pathologic biochemical pathways relevant to patients with end stage renal disease (ESRD) such as accelerated atherosclerosis and dysfunctional erythropoiesis, among others. This review examines the consequences of human protein carbamylation and the clinical impact this is thought to have in patients with ESRD. Recent findings: Recent well-conducted studies across diverse cohorts of patients have independently associated elevations in protein carbamylation to mortality and morbidity in patients with ESRD. Studies are now examining the best strategies to reduce carbamylation load, including interventions aimed at lowering urea levels and restoring amino acid balance. Whether such carbamylation lowering strategies yield clinical improvements remain to be determined. Summary: Numerous fundamental studies provide plausible mechanisms for the observed association between protein carbamylation burden and adverse clinical outcomes in ESRD. Studies employing nutritional and dialytic interventions to lower carbamylation may mitigate this risk but the net clinical benefit has not been established.